Phenomenas of fetishism and mythology between past and present (Journal of Philosophy Culture and Political Science, 2018)
In today’s knowledge, especially in socio-humanitarian, formed not only new conception about being, but also significant modifications in theory of cognitive processes, metrology, there is an active search for explanatory potential of theories, old “limitation” of epistemological ideas are overcoming. That’s why comparative-historical method of scientific analysis become the dominant.The article considers such cultural phenomenas as fetish and myth, which transforms and taking new form, performing particular social and practical function.Key words: fetishism, myth, totemism, archaic, modernity, culture.